First performance test of a 30 mm iron-based superconductor single pancake coil under a 24 T background field. (8th March 2019) - Wang, Dongliang; Zhang, Zhan; Zhang, Xianping; Jiang, Donghui; Dong, Chiheng; Huang, He; Chen, Wenge; Xu, Qingjin; Ma, Yanwei
Abstract: A 30 mm inner diameter iron-based superconductor (IBS) single pancake coil (SPC) was firstly fabricated and tested under a 24 T background field. This SPC was successfully made using the seven-filamentary Ba1−x Kx Fe2 As2 (Ba122) tape by the wind-and-react method. This IBS coil shows the highest I c value at a magnetic field reported so far. For example, the transport critical current of this Ba122 SPC achieved 35 A at 4.2 K and 10 T, which is about half of that of a short sample. This indicates that the non-insulation winding process together with the stainless steel tape is suitable for an IBS. Even more encouraging is the fact that the I c of this SPC is still as high as 26 A under a 24 T background field, which is still about 40% of that at zero external magnetic field. These results clearly demonstrate that IBSs are very promising for high-field magnet applications.